2021
DOI: 10.1186/s12885-021-08018-w
|View full text |Cite
|
Sign up to set email alerts
|

Early discontinuation of PD-1 blockade upon achieving a complete or partial response in patients with advanced melanoma: the multicentre prospective Safe Stop trial

Abstract: Background The introduction of programmed cell death protein 1 (PD-1) blockers (i.e. nivolumab and pembrolizumab) has significantly improved the prognosis of patients with advanced melanoma. However, the long treatment duration (i.e. two years or longer) has a high impact on patients and healthcare systems in terms of (severe) toxicity, health-related quality of life (HRQoL), resource use, and healthcare costs. While durable tumour responses have been observed and PD-1 blockade is discontinued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Therefore, the achievement of CR may be a clinical predictive biomarker for the completion of administration. A durable response after the early completion of ICIs in patients achieving CR or a partial response (PR) is currently being examined in the Safe Stop study on patients with malignant melanoma ( 15 ). The findings obtained will contribute to the establishment of an optimal administration period for ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the achievement of CR may be a clinical predictive biomarker for the completion of administration. A durable response after the early completion of ICIs in patients achieving CR or a partial response (PR) is currently being examined in the Safe Stop study on patients with malignant melanoma ( 15 ). The findings obtained will contribute to the establishment of an optimal administration period for ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were randomized into the continuation and discontinuation groups to compare the survival differences. There are also some clinical trials exploring the modes of determining the treatment duration based on treatment response rather than setting a fixed duration, e.g., the Netherlands Safe Stop study ( 133 ) hopes to answer the question of whether ICIs can be discontinued after achieving CR/PR in melanoma. Moreover, many clinical studies exploring intermittent treatment patterns.…”
Section: Ongoing Clinical Trials Related To Icis Regimen Optimizationmentioning
confidence: 99%
“…A prospective, multicenter single-arm interventional study in the Netherlands, the Safe Stop trial, examined patients with melanoma and a confirmed CR or PR to be included in this study examining early discontinuation of first-line monotherapy with the anti-PD-1 therapies pembrolizumab or nivolumab. The primary objective was to examine the rate of response 24 months following anti-PD-1 treatment discontinuation, with secondary objectives examining BOR and duration of response with need and outcomes of anti-PD-1 rechallenge and associated serious adverse events and health-related quality of life measures ( 49 ).…”
Section: Long-term Outcomes To Icbmentioning
confidence: 99%